The Impact and Challenges of Education and Administration in VET on Economic Growth in Oman During the COVID-19 Period - Alzadjali, Amna; Altinay, Fahriye; Dagli, Gokmen (Frontiers in Psychology, 2022)
The COVID-19 pandemic is still a major global health problem that had substantial consequences on people’s daily lives. This paper evaluates the impact of education and institutional management on Vocational Education and Training (VET) schools in Oman during the COVID-19 period. The purpose of this study is to understand the impact of the COVID-19 pandemic and identify possible challenges that may affect its impact on economic growth. This qualitative research is used as the main methodology of the study. Qualitative data are collected through convenience sampling of 108 VET college students and staff using interviews and questionnaires. The study revealed that the administration plays an important role in economic growth. The students suggested that the national educational administration of the government of Oman plays an important role in their education and that this in turn churns out industry-ready individuals who will impact the economic growth. The government’s role, especially financially post-pandemic lockdown, will be a critical determinant of VET’s impact on economic growth. This study introduces a new perspective on education administration from the perspective of students and staff of VET colleges.